Collaborative information seeking in Pokémon GO - Li, Jiaqi (Nanyang Technological University, 2020)
This dissertation attempted to investigate the information needs of Pokémon GO players and how they collaborate in the information seeking process. The Collaborative information seeking (CIS) phenomenon has been studied in the contexts of professional and leisure activities in recent years, but few have looked into it in gaming scenarios. Pokémon GO is one of the most popular mobile games, which encourages immensely frequent social interactions and collaborations. Assuming the high possibility that the CIS process occurs in Pokémon GO gameplay, we conducted an empirical study through semi-standardized interviews to explore it. The information needs of Pokémon GO players were firstly investigated to form a fundamental understanding of the players’ motivation for information seeking. The interview questions which were designed based on the process-based Collaborative information Seeking model proposed by Chirag Shah (2012c) were then applied to identify collaborative activities in Pokémon GO players’ information seeking processes. The results showcased several conclusions: Pokémon basic information and events information are two categories of information mostly sought after by players; friends via either face-to-face or chat groups are the most popular information source that players refer to for the information they need; CIS process happens frequently in Pokémon GO context; an extension of the process-based CIS model in relation to gaming contexts is recommended.